PERAN GURU DALAM PENGELOLAAN KELAS PADA SISWA KELAS II SDN BAHAGIA 06 BEKASI - Firdayani, Arini; Widiansyah, Apriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the teacher's role in classroom management for second-grade students at SDN Bahagia 06 Bekasi. A descriptive qualitative approach was employed. Research informants—comprising the school principal, the second-grade teacher, second-grade students, and educational staff—were selected using purposive sampling. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The results indicate that the teacher managed the classroom across seven key aspects: teaching readiness, control of student attention, instructional pace and flexibility, implementation of rules and discipline, provision of motivation and reinforcement, handling of classroom disruptions, and enhancement of student engagement. Although challenges such as diverse student characteristics and the limited attention span of some students were encountered, the strategies implemented by the teacher successfully created a conducive learning atmosphere, increased student participation, and supported the achievement of learning objectives. Thus, effective classroom management emerges as a crucial factor in fostering a high-quality learning process in primary schools.